LIMB AMPUTATIONS IN MILITARY PERSONNEL DUE TO ARTILLERY STRIKES IN THE AREA OF THE ANTITERRORIST OPERATION (ATO) IN EAST UKRAINE - Buryanov, A.A.; Bespalenko, A.A.; Tsema, Ie.V.; Dinets, A.V. (The Ukrainian Scientific Medical Youth Journal, 2017)
The aim – to investigate and evaluate amputations of extremities due to the trikes of artillery against military personnel of the Armed Forces of Ukraine (AFU) within the area of the Antiterrorist Operation (ATO) in East Ukraine. Patients and methods. All military personnel of the AFU within ATO was eligible for the study with diagnosis of limb amputations in the period from 01.06.2014 to 30.06.2016, and who were treated in hospitals of the Ministry of Defense of Ukraine. Among 7091 patients with injuries, 152 patients with limb amputations were identified. Results and discussion. Out of 152 patients, 73 (48%) amputations were due to artillery strikes or mine shelling, while other causes of amputation were identified in 79 (52%) of the wounded. Amputations of the middle 1/3 of the arm were more frequently diagnosed in the artillery injury group as compared to the group of another cause of amputation (p = 0.011). The use of artillery by the terrorists against the AFU resulted in more often in amputation of one limb, which was detected in 70 (96%) patients in this group, as compared with 65 (82%) patients in the group of another cause of amputation (p = 0.0093). Analyses of the number of amputated extremities revealed 1 (1.4%) patient with amputation of 2 lower extremities in the artillery fire group, which was 9 times less frequently observed as compared to 9 (11%) patients in the group of another cause of amputation (p = 0.019). Conclusions: The results of the study confirmed significant role of artillery strikes for the amputation of one limb. High-energy artillery weapons play a minor role in terms of amputations at the level of the middle 1/3 of the upper limb and amputation of the two lower limbs.